Characterization of the adaptive response of grapevine (cv. Tempranillo) to UV-B radiation under water deficit conditions. (March 2015) - Martínez-Lüscher, J.; Morales, F.; Delrot, S.; Sánchez-Díaz, M.; Gomès, E.; Aguirreolea, J.; Pascual, I.
Highlights: UV-B and water deficit had little interactive effects on grapevine photosynthesis performance. The impact of UV-B on leaf photosynthesis was overshadowed by the effects of water deficit. Deficit irrigation did not modify the adaptive response of grapevine to UV-B radiation. UV-B and water deficit caused additive effects delaying the phenological development of grape berries. Abstract: This work aims to characterize the physiological response of grapevine ( Vitis vinifera L.) cv. Tempranillo to UV-B radiation under water deficit conditions. Grapevine fruit-bearing cuttings were exposed to three levels of supplemental biologically effective UV-B radiation (0, 5.98 and 9.66 kJ m −2  day −1 ) and two water regimes (well watered and water deficit), in a factorial design, from fruit-set to maturity under glasshouse-controlled conditions. UV-B induced a transient decrease in net photosynthesis ( A net ), actual and maximum potential efficiency of photosystem II, particularly on well watered plants. Methanol extractable UV-B absorbing compounds (MEUVAC) concentration and superoxide dismutase activity increased with UV-B. Water deficit effected decrease in A net and stomatal conductance, and did not change non-photochemical quenching and the de-epoxidation state of xanthophylls, dark respiration and photorespiration being alternative ways to dissipate the excess of energy. Little interactive effects between UV-B and drought were detected on photosynthesis performance, where the impact of UV-B was overshadowed by the effects of water deficit. Grape berry ripening was strongly delayed when UV-B and water deficit were applied in combination. In summary, deficit irrigation did not modify the adaptive response of grapevine to UV-B, through the accumulation of MEUVAC. However, combined treatments caused additive effects on berry ripening.